Epileptologists probe vagus nerve stimulation in children with refractory epilepsy: a promise against sudden unexpected death in epilepsy - Vera C. Terra; Meire A. Nisyiama; João Abrão; Américo C. Sakamoto; Helio R. Machado; Ricardo M. Arida; Esper A. Cavalheiro; Fulvio Alexandre Scorza (Arquivos de Neuro-Psiquiatria)
It is clear that sudden unexpected death in epilepsy (SUDEP) is mainly a problem for people with refractory epilepsy, but our understanding of the best way to its prevention is still incomplete. Although the pharmacological treatments available for epilepsies have expanded, some antiepileptic drugs are still limited in clinical efficacy. In the present paper, we described an experience with vagus nerve stimulation (VNS) treatment by opening space and providing the opportunity to implement effective preventative maps to reduce the incidence of SUDEP in children and adolescents with refractory epilepsy.